Changes in serum desnutrin levels in patients with acne vulgaris - Demir, Betul; Ucak, Haydar; Cicek, Demet; Aydin, Suleyman; Erden, Filter; Dertlioglu, Selma Bakar (John Libbey Eurotext Ltd, 2014)
Background: Androgens and insulin may contribute to increased sebum production in the pathogenesis of acne vulgaris. Objective: We investigated the association between serum desnutrin levels and acne vulgaris in the pathogenesis of insulin resistance. Material and methods: 25 patients presenting with acne vulgaris and 25 control subjects participated in this study. Fasting blood glucose, triglycerides, LDL, VLDL, HDL, total cholesterol, insulin, C-peptide and thyroid function tests were measured. The homeostasis model assessment of insulin resistance (HOMA-IR) was used to calculate insulin resistance. Desnutrin levels were determined by enzyme-linked immunosorbent assay (ELISA) according to the manufacturer's protocol. Results: Patients with acne vulgaris had a mean serum desnutrin level of (8.83 +/- 1.13 mu IU/mL), which was statistically significantly lower in the control group (10:58 +/- 3.43 mu IU/mL). In patients with acne vulgaris the serum glucose levels, insulin levels and HOMA-IR values (87.92 +/- 7:46 mg/dL, 11.33 +/- 5.93 mu IU/mL, 2.49 +/- 1.40, respectively) were significantly higher than the control group (77.36 +/- 9.83 mg/dL, 5.82 +/- 2.68 mu IU/mL, 1.11 +/- 0.51, respectively) (p = 0.01, p<0.001, p<0.001, p<0.001, respectively). Conclusion: Full cohort (patients and controls) evaluation revealed a negative correlation between the serum glucose and desnutrin levels (r = -0.31, p<0.05). A positive correlation was found between insulin and desnutrin levels (r = 0.42, p<0.001). In patients with acne vulgaris, as a result of increased levels of serum glucose and insulin, the function of desnutrin was suppressed, perhaps contributing to insulin resistance.
Keywords: Acne vulgaris; acne diet; desnutrin; insulin resistance